New insights into quercetin nanoformulations for topical delivery - Karan Wadhwa; Varsha Kadian; Vivek Puri; Bigul Yogeshvar Bhardwaj; Ameya Sharma; Rakesh Pahwa; Rekha Rao; Madhu Gupta; Inderbir Singh (Phytomedicine Plus, 2022)
Background: Quercetin is one of the most critical endogenous anti-oxidants used widely in cosmetics, nutraceuticals, and pharmaceuticals products for skincare and therapeutics due to its protective character against oxidants and inflammation. Although low hydrophilicity and poor percutaneous absorption of quercetin make it an untrustworthy entrant for topical delivery, numerous new perspectives have been developed and proposed to overwhelm these problems. Amongst multiple outlooks, nanoparticles-based drug delivery system has gained highlighted attention and showed various advantages in topical delivering a hydrophobic drug like quercetin. Method: The relevant literature was collected from an exhaustive search on databases like PubMed, ScienceDirect, Google Scholar, and others using various keywords, including “quercetin nanoformulations,” “dermal nanoformulations of quercetin,” “quercetin topical formulations,” and many others. Publications in the English language accessed till July 2021 were chosen, whereas non-English language papers, dissertations, unpublished data, and non-original papers were excluded from the study. Results: The present review comprises of various quercetin nanoformulations developed last decade for topical delivery of quercetin. Until recently, numerous nanocarriers systems, including nanovesicles, nanospheres, nanocapsules, nanogels, nanofibres, nanoemulsions, micelles, gold nanoparticles, silica nanoparticles, solid lipid nanoparticles (SLNs), and nanostructured lipid carriers (NLCs), have been developed for skin delivery of quercetin that not only improves the solubility and skin permeability but also augments the physicochemical stability and provides sustain and control release. Conclusions: Nanostructured particles of herbal drugs offer several advantages over other conventional drug delivery systems. Advanced delivery formulations not only help in solving hitches such as poor solubility, bioavailability and stability of quercetin, but also, in the case of topical delivery, overcome the formidable barrier of the skin. Indeed, the application of herbal nanomedicine and herbal nano-drug delivery system is certainly the trend. However, for clinical utilization of such formulations, their investigation in humans needs to be explored. Such exploration along with in depth analysis and dose optimization can pave way for commercial success of quercetin advanced carrier systems for topical application.